Karakteristik Habitat dan Struktur Vegetasi Nepenthes aristolochioides Jebb & Cheek di Taman Nasional Kerinci Seblat: Habitat Characteristics and Vegetation Structure of Nepenthes aristolochioides Jebb & Cheek in Kerinci Seblat National Park - Mandala, Bakti; Zuhud, Ervizal A.M; Rahman, Dede Aulia; Purwati, Betty (Jurnal Silva Tropika, 2026)
ABSTRACT Nepenthes aristolochioides is an endemic and threatened pitcher plant with a restricted distribution in the subalpine ecosystem of Kerinci Seblat National Park. This study aimed to characterize its habitat and associated vegetation structure in the Gunung Tujuh area. Vegetation was sampled using purposive plots centered on Nepenthes aristolochioides individuals and analyzed using the Importance Value Index (IVI). Habitat characterization included topographic, microclimatic, vegetation (NDVI), moisture (NDMI), and soil chemical variables. Nepenthes aristolochioides occurred at elevations of 2,260–2,302 m above sea level under temperatures of 19.4–23.6°C, relative humidity of 82–86%, and slopes of 21.0–31.4%. NDVI (0.367) and NDMI (0.21) indicated moderately open and moist habitat conditions. A total of 44 individuals representing 15 plant species from 10 families were recorded. Ericaceae dominated the sapling, pole, and tree strata, while Urticaceae dominated the seedling layer. Vaccinium miquelii showed the highest IVI at the pole stage (165.27%), whereas Diplycosia heterophylla dominated the tree layer (111.87%). Soil was slightly acidic (pH 6.07–6.23) with relatively high nutrient availability, and no prey was observed in mature pitchers. These findings provide baseline ecological information to support habitat management and conservation of this endangered endemic species.   Keywords: habitat characteristics, Nepenthes aristolochioides, subalpine ecosystem, vegetation structure, conservation ABSTRAK Nepenthes aristolochioides merupakan tumbuhan kantong semar endemik Sumatra yang berstatus terancam dan memiliki sebaran terbatas di ekosistem subalpin Taman Nasional Kerinci Seblat. Informasi mengenai karakteristik habitat dan struktur vegetasi yang mendukung keberadaan spesies ini masih terbatas. Penelitian ini bertujuan untuk menganalisis karakteristik habitat dan struktur vegetasi Nepenthes aristolochioides di kawasan Gunung Tujuh. Pengumpulan data dilakukan menggunakan metode purposive sampling dengan plot pengamatan yang berpusat pada individu Nepenthes aristolochioides. Analisis vegetasi dilakukan pada tingkat semai, pancang, tiang, dan pohon menggunakan Indeks Nilai Penting (INP), sedangkan karakteristik habitat dianalisis berdasarkan faktor topografi, mikroklimat, indeks vegetasi (NDVI), indeks kelembapan (NDMI), dan sifat kimia tanah. Hasil penelitian menunjukkan bahwa Nepenthes aristolochioides tumbuh pada ketinggian 2.260–2.302 mdpl dengan suhu 19,4–23,6°C, kelembapan udara 82–86%, serta habitat yang relatif terbuka dan lembap (NDVI 0,367; NDMI 0,21). Sebanyak 44 individu yang tergolong ke dalam 15 spesies dan 10 famili berhasil diidentifikasi. Vegetasi didominasi oleh famili Ericaceae pada tingkat pancang, tiang, dan pohon, sedangkan tingkat semai didominasi oleh Urticaceae. Vaccinium miquelii memiliki nilai INP tertinggi pada tingkat tiang, sedangkan Diplycosia heterophylla mendominasi tingkat pohon. Hasil penelitian ini menyediakan informasi dasar mengenai karakteristik habitat dan struktur vegetasi Nepenthes aristolochioides yang dapat menjadi dasar ilmiah bagi pengelolaan habitat dan upaya konservasi spesies endemik yang terancam ini.   Kata kunci: karakteristik habitat, Nepenthes aristolochioides, struktur vegetasi, subalpin, konservasi